(untitled) (Research, Society and Development, 2023)
Plastic surgery is an area of wide activity and performs a set of clinical and surgical procedures with the objective of repairing and reconstructing parts of the human lining. Brazil appears as the second country that most performs plastic surgeries in the world, with abdominoplasty being one of the most frequent. For the elaboration of the work, the integrative bibliographic review methodology was used. Abdominoplasty is a procedure that aims to remove skin and fat, as well as restructure weakened muscles and abdominal fascia. This review aims to analyze the surgical indications, the preoperative period, the surgical techniques and the risks of abdominoplasty. It concludes through this study that there are several techniques for performing abdominoplasty. To choose the best method, the plastic surgeon must take into account the technical criteria proven in the medical literature and the patient’s desire.